Odpowiedzi

Najlepsza Odpowiedź!
2009-12-22T21:29:49+01:00
A) V=Vo+Vrazy t Xo , t
V = V₀+VtX₀ / -V₀
V - V₀ = VtX₀ / :VX₀
(V - V₀)/VX₀ = t
t = (V - V₀)/VX₀

b) m1 razy V1+m2 razy v2=(m1+m2) razy v3 V1,V3,m1
m₁*V₁+m₂*V₂= (m₁+m₂)* V₃

wyznaczam V₃:

m₁*V₁+m₂*V₂= (m₁+m₂)* V₃ /:(m₁+m₂)
V₃ = (m₁*V₁+m₂*V₂) / (m₁+m₂)

Wyznaczam V₁:

m₁*V₁+m₂*V₂= (m₁+m₂)* V₃
m₁*V₁ = (m₁+m₂)* V₃ - m₂*V₂ / :m₁
V₁= ((m₁+m₂)* V₃ - m₂*V₂) / m₁

Wyznaczam m₁:

m₁*V₁+m₂*V₂= (m₁+m₂)* V₃
m₁*V₁ + m₂V₂ = m₁V₃ + m₂V₃
m₁*V₁ - m₁V₃ = m₂V₃ -m₂V₂
m₁(V₁ - V₃) =m₂(V₃ -V₂) /:(V₁ - V₃)
m₁ = (m₂(V₃ -V₂))/(V₁ - V₃)

c) P=2razy(a razy b + b razy c + a razy c) a
P = 2*(ab +bc +ac)

wyznaczam a:
P = 2ab +2bc +2ac
P - 2bc = 2ab + 2ac
P - 2bc = a(2b + 2c) /:(2b + 2c)
(P - 2bc)/(2b + 2c) = a
a = (P - 2bc)/(2b + 2c)